Impact of drying process on kraft lignin: lignin-water interaction mechanism study by 2D NIR correlation spectroscopy - Oihana Gordobil; René Herrera; Faksawat Poohphajai; Jakub Sandak; Anna Sandak (Journal of Materials Research and Technology, 2021)
Kraft lignin, an industrially available by-product from the pulp and paper industry, has revealed enormous potential to be valorised into a wide range of chemicals and biomaterials in the last two decades. However, the understanding of lignin chemistry remains challenging due to its chemical complexity. The goal of this work was to investigate the effect of drying temperature on the chemical, physical, and hygroscopic properties of hardwood kraft lignin isolated from industrial black liquor and elucidate the molecular interactions occurring between water and kraft lignin. Sorption-desorption isotherms determined by dynamic vapour sorption (DVS) technique revealed that the drying process considerably affected the hygroscopicity of the lignin polymer. Moreover, analytical pyrolysis (Py–GC–MS), dynamic NIR spectra collected as a function of relative humidity (0–95%) during sorption-desorption cycles and principal component analysis (PCA), evidenced chemical differences between lignin dried at room (25 °C) temperature and mild oven (55 °C) conditions. The main spectral changes associated with the water sorption in kraft lignin samples were analyzed using difference spectrum technique. 2D NIR spectral correlation analysis provided water sorption mechanism of lignin polymer, disclosing for the first time the sequential order in which water vapour molecules interact with active sorption sites in kraft lignin.